2009
DOI: 10.1148/radiol.2511081300
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Body PET/CT Scanning: Estimation of Radiation Dose and Cancer Risk

Abstract: Whole-body PET/CT scanning is accompanied by substantial radiation dose and cancer risk. Thus, examinations should be clinically justified, and measures should be taken to reduce the dose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
306
0
7

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 429 publications
(323 citation statements)
references
References 21 publications
10
306
0
7
Order By: Relevance
“…Previous studies reported an increased secondary cancer risk due to surveillance CT scans in patients with NHL [18,19]. As regards to the use of 18 F-FDG-PET/CT, it is well known that involves exposure to a substantial dose of ionising radiations, again with increasing cancer risk [20]. However, 18 F-FDG-PET/CT has a crucial role in FL management.…”
Section: Imaging Monitoring and Wwmentioning
confidence: 99%
“…Previous studies reported an increased secondary cancer risk due to surveillance CT scans in patients with NHL [18,19]. As regards to the use of 18 F-FDG-PET/CT, it is well known that involves exposure to a substantial dose of ionising radiations, again with increasing cancer risk [20]. However, 18 F-FDG-PET/CT has a crucial role in FL management.…”
Section: Imaging Monitoring and Wwmentioning
confidence: 99%
“…More recently, it has become possible to integrate cardiac and coronary artery imaging into chest CT examinations, a concept applicable to numerous thoracic diseases [5]. The consequence of such developments is the substantial increase in the radiation dose delivered to patients, individually but also collectively [6], and the subsequent risks, even small, of cancer induction by lowlevel radiation [7,8]. Facing the challenge of providing diagnostic image quality at the lowest radiation dose, the radiological community has modified chest CT protocols at the pace of new technology implementations aiming to reduce radiation exposure, such as anatomical tube current modulation, ECG-controlled tube current modulation or dynamically adjustable pre-patient collimation of the X-ray beam in the z-axis direction [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…It carries a 1.5-2 times greater dose of radiation than conventional CT chest abdomen pelvis depending on the protocol. 4 It does, however, provide a clear, non-invasive method for confirming a diagnosis that is otherwise difficult to make with good sensitivity and specificity. 5,6 Delayed diagnosis of large vessel vasculitis could result in vessel occlusion or aneurysmal formation and lead to significant mortality ranging from 3-21%.…”
Section: Discussionmentioning
confidence: 99%